An examination of nervous system revealed unexpected immunoreactivity of both secretory apparatus and excretory canals in plerocercoids of two broad tapeworms (Cestoda: Diphyllobothriidea) - Daniel Barčák; Anna Alexovič Matiašová; Eva Čisovská Bazsalovicsová; Miroslava Soldánová; Mikuláš Oros; Ivica Králová-Hromadová (Parasitology, 2023)
Dibothriocephalus ditremus and Dibothriocephalus latus are diphyllobothriidean tapeworms autochthonous to Europe. Their larval stages (plerocercoids) may seriously alter health of their intermediate fish hosts (D. ditremus) or cause intestinal diphyllobothriosis of the final human host (D. latus). Despite numerous data on the internal structure of broad tapeworms, many aspects of the morphology and physiology related to host–parasite co-existence remain unclear for these 2 species. The main objective of this work was to elucidate functional morphology of the frontal part (scolex) of plerocercoids, which is crucial for their establishment in fish tissues and for an early attachment in final hosts. The whole-mount specimens were labelled with different antibodies and examined by confocal microscope to capture their complex 3-dimensional microanatomy. Both species exhibited similar general pattern of immunofluorescent signal, although some differences were observed. In the nervous system, FMRF amide-like immunoreactivity (IR) occurred in the bi-lobed brain, 2 main nerve cords and surrounding nerve plexuses. Differences between the species were found in the structure of the brain commissures and the size of the sensilla. Synapsin IR examined in D. ditremus occurred mainly around FMRF amide-like IR brain lobes and main cords. The unexpected finding was an occurrence of FMRF amide-like IR in terminal reservoirs of secretory gland ducts and excretory canals, which has not been observed previously in any tapeworm species. This may indicate that secretory/excretory products, which play a key role in host–parasite relationships, are likely to contain FMRF amide-related peptide/s.